2006
DOI: 10.1136/jcp.2005.034199
|View full text |Cite
|
Sign up to set email alerts
|

Nasal natural killer/T-cell lymphoma and its association with type “i”/XhoI loss strain Epstein–Barr virus in Chile

Abstract: Although nasal NK/T-cell lymphomas from Chile share similar clinicopathological features, high association with EBV and unfavourable prognosis with those described elsewhere, genotype analysis shows that the new recombinant type "i"/XhoI loss strain might contribute to explain the intermediate incidence of nasal NK/T-cell lymphomas in Latin America.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 35 publications
2
13
0
1
Order By: Relevance
“…The number of patients were similar to some seen in multicentre studies [2, 13, 15, 2022, 3236]. The present study shows that the clinical characteristics of nasal NKTCL in Peru are similar to those described in other Latin American as well as Asian and Western countries [2, 3, 6, 8, 9, 29, 30]. The treatment used in our population was according to the clinical staging, with radiotherapy only or concurrent with chemotherapy for early stages, and chemotherapy only for advanced disease, as is described in the international literature [31].…”
Section: Discussionsupporting
confidence: 88%
“…The number of patients were similar to some seen in multicentre studies [2, 13, 15, 2022, 3236]. The present study shows that the clinical characteristics of nasal NKTCL in Peru are similar to those described in other Latin American as well as Asian and Western countries [2, 3, 6, 8, 9, 29, 30]. The treatment used in our population was according to the clinical staging, with radiotherapy only or concurrent with chemotherapy for early stages, and chemotherapy only for advanced disease, as is described in the international literature [31].…”
Section: Discussionsupporting
confidence: 88%
“…Our study indicated that EBV type A was predominantly found in ENKTL, similar to previous reports from Japan, Thailand, Mexico, Chile, Brazil, and Spain [13][14][15][16]. However, in Peru and the USA, type B was found in the majority of ENKTL cases [17,18].…”
supporting
confidence: 89%
“…This novel recombinant strain was originally described in healthy donors 17 and later in nasal NK/T-cell lymphoma. 18 Thus this current case is the first evidence that type ''i''/XhoI loss EBV strain can be found in a LELC tumor. This is an important finding since to date the presence of type ''i''/XhoI loss EBV strain has been described in lymphoid tumors but not in epithelial tumors.…”
Section: Discussionmentioning
confidence: 56%
“…Immunohistochemical stains were performed on representative formalin-fixed paraffin sections at our institution using the streptavidin-biotin-peroxidase complex technique and an automated tissue stainer (Biogenex, San Ramon, CA) with antibodies specific for keratins (AE1/AE2) (dilution 1:100, Biogenex), HMB45 (dilution 1:50, Biogenex), and EBV EBNA-1 (dilution 1:50, DAKO, Carpenteria, CA). 18 …”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation